A Rapid Semi-automated Literature Review on Legal Precedents Retrieval - Silva, Hugo (2022)
Silva, H., António, N., & Bacao, F. (2022). A Rapid Semi-automated Literature Review on Legal Precedents Retrieval. In G. Marreiros, B. Martins, A. Paiva, B. Ribeiro, & A. Sardinha (Eds.), Progress in Artificial Intelligence: 21st EPIA Conference on Artificial Intelligence, EPIA 2022, Lisbon, Portugal, August 31–September 2, 2022, Proceedings (pp. 53-65). (Lecture Notes in Artificial Intelligence; Vol. 13566). Springer, Cham. https://doi.org/10.1007/978-3-031-16474-3_5. Funding Information: This research was supported by a grant from the Portuguese Foundation for Science and Technology (“Fundação para a Ciência e a Tecnologia”) [grant number DSAIPA/DS/0116/2019].